Design of Immunobiosensors for Detection of Tumor-Associated Anti-P53 Autoantibodies: Method Development - Adeniyi, Omotayo Kayode (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
Detection and profiling of circulating tumor-associated autoantibodies (TAAbs) are useful for screening and early-stage diagnosis of asymptomatic lung cancer. Immunobiosensor technologies aimed to accomplish the highly sensitive, rapid and low-cost detection of TAAbs can improve the early-stage detection of lung cancer. Immunobiosensors for the detection of anti-P53-tumour associated autoantibodies have been developed in this work. The design of sensing interfaces with immobilized P53 protein (P53ag) as a sensing element layer on a solid interface was investigated. Several methods of detecting anti-P53-antibodies (anti-P53ab) were investigated. These methods are label-free detection using electrochemical impedance spectroscopy (EIS) and two label techniques. The label-free electrochemical techniques utilize gold electrode pre-modified with a conducting layer of electrochemically grafted phenylethylamine for covalent immobilization of P53ag. The limit of anti-P53ab detection with the label-free EIS was 103.0 pg.ml-1. The labeled technique developed utilizes fluorescent, and peroxidase-like nanomaterial labeled antibody as a detection probe. For the fluorescence detection, fluorescent silica nanoparticles were synthesized by overloading FITC into the silica matrix and conjugated to detection antibody (anti-IgG). The detection of the anti-P53ab was based on the dissolution of the silica nanoparticles to release the loaded dye as a signal amplification strategy. The fluorescence detection was carried out on a microplate, and magnetic bead modified P53-antigen platforms and limit of detection (LoD) were 42.0 fg.ml-1 and 3.3 fg.ml-1 for anti-P53ab; respectively. Fe3O4@SiNP-APTES-Au@Pd hybrid nanoparticles were synthesized, and their peroxidase-like activity and colorimetric detection were evaluated. The Fe3O4@SiNP-APTES-Au@Pd exhibited comparable activity to HRP. The Fe3O4@SiNP-APTES-Au@Pd was conjugated to protein-G-anti-IgG for the detection of anti-P53ab on a microplate and cellulose paper platforms. The LoD was 20.0 fg.ml-1 and 63.0 fg.ml-1 for the microplate and cellulose paper platform; respectively. The potential application of the designed immunobiosensor was evaluated in simulated serum samples. The developed sensors showed higher detection sensitivity, stability and had a lower detection limit for anti-P53ab when compared with the ELISA based detection. The results have provided alternative and effective quantification approaches to ELISA and a promising future for multiplexed detection of tumor-associated autoantibodies. The developed methodologies in this thesis could be applied for the detection of other autoantibodies in other cancer types and auto-immune diseases.
Keywords: Lungs -- Cancer -- Early detection; Autoantibodies; Biosensors; Immunochemistry; Biochemical markers; p53 antioncogene